The Effect Of Administering Iron Tablets (Fe) On Increasing Haemoglobin Levels In Postpartum Mothers At Merauke Hospital - Maria Magdalena Hindom; Reny yuli Astutik; Riza Tsalatsatul Mufidah; Tety Ripursari (Journal of Health Science Community, 2024)
Postpartum mothers experience a decrease in Hb levels due to bleeding during childbirth, postpartum bleeding can cause death. Predisposing factors include anemia. Efforts to prevent and control anemia in postpartum mothers by administering Fe tablets for 3 weeks. In theory, Fe tablets really help the absorption of iron. To identify and analyze the effect of giving Fe tablets on increasing HB levels in postpartum women in the Merauke Regional Hospital Work Area in 2023. Quasi experimental with a One Group design which was studied twice, namely pre-test and post-test. The population was all postpartum mothers. Sample of 30 people using purposive sampling. The statistical test used is the independent sample t test. Research results: Show that the average Hb level before consuming Fe tablets was 12,521 g/dl and the average Hb after consuming Fe tablets was 14,039 after 3 weeks with an increase in Hb levels of 1,518 g/dl. In the intervention group, the average initial Hb level was 10.4 g/dl. The average increase in Hb level was 0.7 g/dl in 3 weeks. Conclusion: The results of statistical tests show that there is an effect of giving Fe tablets on Hb levels in postpartum women with a p value of 0.000 (p < 0.05). There is a significant influence. by administering Fe tablets to Hb levels in postpartum mothers. Before and after administering Fe tablets can help increase Hb levels.